Reading Kazuo Ishiguro in Times of Crisis. Issue 7 (3rd October 2022) - Groes, Sebastian; Dean, Dominic
ABSTRACT: International crises are central to Kazuo Ishiguro's work. This introduction situates Ishiguro alongside contemporary global emergencies, including the COVD-19 pandemic, climate change, and reactions to emancipatory movements. It suggests that Ishiguro's work interrogates 'crisis' by confronting his characters with both individual and collective crises, a theme explored in Catherine Charlwood's essay here. It shows how Ishiguro's work indirectly relates to the vast health crisis of COVID-19, which Sebastian Groes explores in his essay on empathy, (robot) ethics, digital well-being, and inequality. Connected to the pandemic, the introduction traces how Ishiguro's writing evidences growing concern for the climate crisis. The politics of migration are a key theme in Ishiguro: here Dominic Dean explores their longstanding and dangerous relationship with conspiracy theories, while Ivan Stacy, Melinda Dabis and Richard Robinson all connect Ishiguro to anxieties over resurgent nationalisms, cosmopolitan internationalisms, and complex transnationalisms. This introduction sets out how the essays in this Special Issue collectively explore the ethical difficulties in Ishiguro's crisis narratives, their refusals of easily satisfying resolutions, and their implicit critique of crisis frameworks for understanding political and historical problems. Sharply distinct from passivity or disinterest, Ishiguro's work elicits an attitude of humility against apparently perpetual, end-dominated crises.